1982
DOI: 10.1107/s0021889882011510
|View full text |Cite
|
Sign up to set email alerts
|

The polymorphism of silver tungstate Ag2WO4

Abstract: Crystal data for α‐, β‐ and γ‐Ag2WO4 were collected from Cu Kα1 powder diagrams, α‐Ag2WO4 is orthorhombic (Pn2n) with a = 10.820(2), b = 12.018(2) and c = 5.900(1) Å. β‐Ag2WO4 is hexagonal (P63 or P63/m) with a = 11.0925(3) and c = 7.5424(4) Å. γ‐Ag2WO4 is cubic (Fd3m, spinel type) with a = 9.352(1) Å.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
46
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 1 publication
0
46
0
Order By: Relevance
“…[22] Amongt hose polymorphs a-Ag 2 WO 4 is thermodynamically most stable [22] and belongs to orthorhombic symmetry Pn2n. [22] Amongt hose polymorphs a-Ag 2 WO 4 is thermodynamically most stable [22] and belongs to orthorhombic symmetry Pn2n.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] Amongt hose polymorphs a-Ag 2 WO 4 is thermodynamically most stable [22] and belongs to orthorhombic symmetry Pn2n. [22] Amongt hose polymorphs a-Ag 2 WO 4 is thermodynamically most stable [22] and belongs to orthorhombic symmetry Pn2n.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, introducing am onovalentc ation such as Ag favors ac omplicated network structure of silver tungstate (Ag 2 WO 4 ), which can exhibit three different structuralp hases; a-, b-, and g-Ag 2 WO 4 . [22] Amongt hose polymorphs a-Ag 2 WO 4 is thermodynamically most stable [22] and belongs to orthorhombic symmetry Pn2n. [22,23] All tungsten atoms are six-coordinate and form WO 6 octahedra.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Ag 2 WO 4 belongs to the oxoargentates family, 2 and it is an inorganic material containing a rich variety of polymorphs: α-orthorhombic (α-Ag 2 WO 4 ) with a space group of Pn2n, β-hexagonal with a space group of P63/m, and γ-cubic with a space group of Fd3m depending on the acid or alkaline pH range. 3,4 The orthorhombic structure of α-Ag 2 WO 4 exhibits a complex network composed of [WO 6 ] and [AgO y ] (y = 7, 6, 4, and 2) moieties as constituent clusters of this material whose internal vibration spectra provide information on the structure and order−disorder effects in crystal lattices. 5,6 This structural pattern is a key characteristic for a complete understanding of α-Ag 2 WO 4 potentialities.…”
Section: Introductionmentioning
confidence: 99%
“…4,16,17 Tungsten-based oxides are an important class of materials that display wide potential functional properties, [18][19][20] speci-cally the silver tungstate (Ag 2 WO 4 ) compound, which can exhibit three different structures: a-orthorhombic, b-hexagonal, and g-cubic. [21][22][23][24][25] Recently, our research group reported a detailed study of the synthesis, structural and optical properties of hexagonal nanorod-like elongated a-Ag 2 WO 4 nanocrystals obtained by different methods.…”
mentioning
confidence: 99%